IMPACT OF CULTURAL EXPRESSIONS ON THE DEVELOPMENT OF LANGUAGE. (Лучшие интеллектуальные исследования, 2025)
Abstract: Cultural expressions are one of the important factors in language development. Language is the most complex and rich means of communication of mankind, the development of which occurs under the influence of many factors. Culture, on the other hand, is the main element that determines the context, content and shape of the language. Cultural expressions ensure the beauty, richness and originality of the language, while also significantly contributing to the development of the language.